Impact of irrigation and mulching method on soil properties and date palm Phoenix dactylifera L. productivity - Alhamd, Abdulrahman D. (Basrah Journal Of Date Palm Research, 2024)
Aim of good soil and water management and the use of modern irrigation technology is to reduce water waste and increase the efficiency of its use, as it is important to adopt irrigation methods that ensure the balance of water salinity in the soil in proportion to crop growth and productivity. A field experiment was conducted in private date palm orchards in Hamdan/Abu Al-Khasib district, 10 km south of Basrah city, during the two growing seasons 2020-2021, on a land of 4 dunums, the aim of studying is the Impact of irrigation and mulching method on soil properties and date palm. The results showed that using irrigation from above by basin and drip irrigation led to an increase in soil moisture content, a decrease in soil electrical conductivity values, and an increase in palm productivity (weight, length, total sugars, and total yield) compared to using the traditional irrigation method (tidal). The results showed that the use of mulching for the irrigation basin significantly contributed to increasing the moisture content of the soil and decreasing the electrical conductivity values for different depths, especially when using mulching with polyethylene. The traditional irrigation method (tidal), which prepares water using subsurface irrigation, is no longer sufficient to provide the moisture necessary for the growth and productivity of palm trees. Therefore, other irrigation methods must be followed, such as using basin and drip irrigation, and improving environmental conditions using a soil mulching system.